(untitled) (Revista Contexto & Saúde, 2024)
Introduction: Childhood caries remains a major public health issue in Brazil’s impoverished communities. Although government-sponsored programs have targeted improvement of oral health in children from public schools, more information is needed on the effectiveness of these programs. Objective: The objective was to analyze the prevalence and factors associated with caries in children aged 5 and 12 years in public versus private schools. Methods: This cross-sectional study included 857 children aged 5 (n=509) and 12 years (n=348) who attended public (n=416) or private (n=441) schools in Patos, PB-Brazil. Between March–September 2018 we examined caries from this study population using the DMFT/dmft index and obtained data on its demographics, toothbrushing frequency, socioeconomic status and schools’ oral health program and services via questionnaires. Statistical analyses were performed using multiple logistic regression (p<0.05). Results: Among 5-years-old children from public vs private schools, untreated caries prevalence was 51.5% (n=117) vs 28.4% (n=80) and dmft index, 2.34 vs 1.04. In 12-years-old children, untreated caries prevalence of 41.3% (n=78) and DMFT index=0.99 in public and of 22% (n=35) and DMFT index=0.50 in private schools were observed. Public school children showed 2.19 (5-years-old) and 2.41 (12-years-old) higher caries odds than private school children (p<0.01). Among 5-years-old children, caries odds were 3.6 higher in low-income households (p=0.025) and 42% lower in children who received periodical dental visits at schools (p=0.011). Conclusion: Children aged 5 and 12 from public schools had higher caries odds than children from private schools. At 5 years old, households with higher incomes and access to dental care in public schools can decrease the odds of dental caries.